The largest sauropodomorph skull from the Lower Jurassic Lufeng Formation of China - Qian-Nan Zhang; Lei Jia; Tao Wang; Yu-Guang Zhang; Hai-Lu You (PeerJ)
The Lower Jurassic Lufeng Formation of China has long been recognized for its diverse early-diverging sauropodomorph dinosaurs, with eight genera and ten species, representing more than half the Laurasian records. In this paper, we describe a new genus and species of non-sauropodan sauropodomorph, Lishulong wangi gen. et sp. nov., from Yunnan Province in southwestern China. This new taxon is represented by a partial skeleton including the skull and nine articulated cervical vertebrae, which differs from other Lufeng forms in both cranial and cervical characteristics. It bears several autapomorphies of the nasal process, the maxillary neurovascular foramen, and the cervical neural spine. Phylogenetic analysis reveals that Lishulong is an early-diverging member of the Sauropodiformes, and the sister-taxon of Yunnanosaurus. Elucidating the novel osteology of Lishulong, it possessed the largest sauropodomorph cranial material currently identified from the Lufeng Formation, not only enriches the diversity of the Lufeng dinosaur assemblage, but also enhances our understanding of the character evolution in early-diverging sauropodiforms. Furthermore, information about paleobiogeographic distributions indicates that Early Jurassic sauropodomorphs, especially Chinese taxa, have maintained multiple dispersions and exchanges within Pangaea.